Pengembangan E-Modul Interaktif Berbasis Discovery Learning untuk Meningkatkan Kemampuan Literasi Siswa Kelas XI - I Komang Budiasa; I Wayan Sukra Warpala; I Gde Wawan Sudatha (Jayapangus Press, 2026)
This study aims to develop a valid, practical, and effective interactive e-module based on discovery learning to improve the literacy skills of Year 11 students at SMA Negeri 1 Selat. The development of the e-module was motivated by the students’ need for more engaging and interactive learning materials. This study was conducted using the ADDIE model, which comprises the stages of analysis, design, development, implementation and evaluation. The research subjects were Year 11 students at SMA Negeri 1 Selat. The data collection methods used were observation, questionnaires and tests. The data analysis methods employed were qualitative descriptive analysis, quantitative descriptive analysis, inferential statistical analysis using the t-test, the N-Gain test and Cohen’s d test. The research results indicate that the interactive e-module was deemed valid based on a content expert validation score of 90.4%, a media expert validation score of 92.8%, and a design expert validation score of 95.5%. The e-module developed was deemed practical, with an average score of 91%. Furthermore, the e-module was found to be effective based on the results of a paired-sample t-test with a p-value of < 0.005, indicating a significant difference in students’ literacy skills before and after using the interactive e-module. The N-Gain test yielded a value of 0.6264, representing a percentage of 62.64%, indicating that the interactive e-module is sufficiently effective in improving literacy skills. The Cohen’s d test yielded a value of 2.138, indicating that the interactive e-module has a significant effect on improving literacy skills. It can therefore be concluded that the discovery-learning-based interactive e-module developed is valid, practical and effective in improving the literacy skills of Year 11 students at SMA Negeri 1 Selat.